2020
DOI: 10.1021/acsanm.9b02550
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Multidimensional Assembly and Sintering of CuInS2 Nanoparticles into Lamellar Nanosheets with Band Gap Narrowing

Abstract: Two-dimensional (2D) nanomaterials have fascinating structural, electrical, and optical properties, especially strong excitonic effects due to decreased dielectric screening. However, constructing 2D ultrathin nanomaterials, with the exception of layered materials, remains a challenge. Herein, we successfully realize oriented attachment on guiding one-dimensional chalcopyrite CuInS 2 nanocrystal (NC) formation and 2D assembly into lamellar nanosheets by applying pressure-driven sintering of zero-dimensional Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…To the best of our knowledge, this is the largest piezochromic PL tuning range in the visible light range for traditional inorganic semiconductor nanomaterials. 26,35,36 Simultaneously, an ultrabroad bandgap tunability range was observed from 1.99 eV (0 GPa) to 2.45 eV (approximately 14.2 GPa). In addition, in situ small-angle synchrotron X-ray scattering (SAXS) measurements and transmission electron microscopy (TEM) images demonstrated that core–shell InP/ZnSe NCs were sintered under high pressure, resulting in the formation of two-dimensional (2D) nanostructures.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…To the best of our knowledge, this is the largest piezochromic PL tuning range in the visible light range for traditional inorganic semiconductor nanomaterials. 26,35,36 Simultaneously, an ultrabroad bandgap tunability range was observed from 1.99 eV (0 GPa) to 2.45 eV (approximately 14.2 GPa). In addition, in situ small-angle synchrotron X-ray scattering (SAXS) measurements and transmission electron microscopy (TEM) images demonstrated that core–shell InP/ZnSe NCs were sintered under high pressure, resulting in the formation of two-dimensional (2D) nanostructures.…”
Section: Introductionmentioning
confidence: 86%
“…19 Our previous reports have confirmed that InP/ZnS NCs exhibit remarkable piezochromic behavior, where the color changes from orange to green. 26 Compared with the 7.7% lattice mismatch rate between ZnS and InP, the lattice mismatch rate between ZnSe and InP is only 3.2%. 1 Thus, there is a narrow emission spectrum for InP/ ZnSe as compared to InP/ZnS, which ensures the luminescence purity of InP/ZnSe NCs and provides more pronounced color changes for piezochromic behavioral studies.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Quantum dots (QDs) are appealing nanoscale stress/strain sensing materials (SSMs) because of their small size, high photoluminescence (PL) intensity, and tunable band gap governed by the quantum confinement effect. For example, the potential of QDs applied to detect the pressure induced by explosion, shock, or extreme conditions in experimental biology is enormous due to their GPa-level pressure-sensitive merits. Moreover, QDs can also be employed for in situ stress/strain detection in highly heterogeneous materials because of their nanometer size . Based on the potential of QDs for stress/strain sensing, the PL responses of QDs related to external pressure under several loading conditions have been studied over the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…Besides manipulating interatomic distances and inducing structural phase transitions at atomic scales, studies have shown that high pressure has the ability to tune interparticle distances in nanocrystal (NC) assemblies and induce their mesoscale phase transitions and morphological changes. To date, the pressure-induced NC assembly and coalescence process has been successfully applied for synthesis of 1–3D nanostructures for various metal or semiconductor NCs. …”
mentioning
confidence: 99%